Food composition and analysis : methods and strategies - Haghi, A. K; Carvajal-Millan, Elizabeth (Apple Academic Press, 2014)
This book covers methods and strategies related to food composition and analysis. Topics include antioxidant activity of maize bran arabinoxylan microspheres; active packaging based on the release of carvacrol and thymol for fresh food; enzymes for the flavor, dairy, and baking industries; membrane technology in food processing; tenderization of meat and meat products; biological properties of mushrooms; polyacrylamide-grafted gelatin; irradiation of fruits, vegetables, and spices for better preservation and quality; oilseeds as a sustainable source of oil and protein for aquaculture feed.>